ln(4x-10)=ln(2x+4)

Simple and best practice solution for ln(4x-10)=ln(2x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(4x-10)=ln(2x+4) equation:


Simplifying
ln(4x + -10) = ln(2x + 4)

Reorder the terms:
ln(-10 + 4x) = ln(2x + 4)
(-10 * ln + 4x * ln) = ln(2x + 4)
(-10ln + 4lnx) = ln(2x + 4)

Reorder the terms:
-10ln + 4lnx = ln(4 + 2x)
-10ln + 4lnx = (4 * ln + 2x * ln)
-10ln + 4lnx = (4ln + 2lnx)

Solving
-10ln + 4lnx = 4ln + 2lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-4ln' to each side of the equation.
-10ln + -4ln + 4lnx = 4ln + -4ln + 2lnx

Combine like terms: -10ln + -4ln = -14ln
-14ln + 4lnx = 4ln + -4ln + 2lnx

Combine like terms: 4ln + -4ln = 0
-14ln + 4lnx = 0 + 2lnx
-14ln + 4lnx = 2lnx

Add '-2lnx' to each side of the equation.
-14ln + 4lnx + -2lnx = 2lnx + -2lnx

Combine like terms: 4lnx + -2lnx = 2lnx
-14ln + 2lnx = 2lnx + -2lnx

Combine like terms: 2lnx + -2lnx = 0
-14ln + 2lnx = 0

Factor out the Greatest Common Factor (GCF), '2ln'.
2ln(-7 + x) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-7 + x)' equal to zero and attempt to solve: Simplifying -7 + x = 0 Solving -7 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + x = 0 + 7 x = 0 + 7 Combine like terms: 0 + 7 = 7 x = 7 Add '-1x' to each side of the equation. x + -1x = 7 + -1x Combine like terms: x + -1x = 0 0 = 7 + -1x Simplifying 0 = 7 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| (7/8)2+5y | | 2x^2-41x=-7x^2-6x-24 | | 6x/(x^2+3)^2=0 | | (7/8)0+5y | | 3xy^3= | | 21/15=3k-2/5 | | 4x+1=84 | | 6x^2+4x-14=35-31x | | 6y^3-4y^2-16y=0 | | x-2/6=-5 | | 12/3w=36/63 | | 3x+23=11x+47 | | 3x+1=38 | | 6y^3-16y^2-16y=0 | | 0.6=2*x | | 4g+9=13 | | 2(x+1)+3x=37 | | 4x-3+5x=6x-3+3x | | x/3+4=37 | | 4.8d=1.3d-21 | | 2(x+1)+3x=27 | | x/8=12/32 | | 2+4y=6 | | 2(x+1)3x=37 | | 2x-5=36 | | p^3+2p^2-4p-8=0 | | 9x-7=4x-7+5x | | m/-6=8 | | 4f+7=9 | | (3x+2)2+(4x-3)2=(5x-1)2 | | 6x^3+x^2+x=0 | | 6x^2+19x+7=-1 |

Equations solver categories